3-D surface profilometry based on modulation measurement by applying wavelet transform method. (January 2017) - Zhong, Min; Chen, Feng; Xiao, Chao; Wei, Yongchao
Abstract: A new analysis of 3-D surface profilometry based on modulation measurement technique by the application of Wavelet Transform method is proposed. As a tool excelling for its multi-resolution and localization in the time and frequency domains, Wavelet Transform method with good localized time-frequency analysis ability and effective de-noizing capacity can extract the modulation distribution more accurately than Fourier Transform method. Especially for the analysis of complex object, more details of the measured object can be well remained. In this paper, the theoretical derivation of Wavelet Transform method that obtains the modulation values from a captured fringe pattern is given. Both computer simulation and elementary experiment are used to show the validity of the proposed method by making a comparison with the results of Fourier Transform method. The results show that the Wavelet Transform method has a better performance than the Fourier Transform method in modulation values retrieval. Highlights: 1D Morlet Wavelet Transform method is proposed to the modulation retrieval in the 3-D Surface Profilometry. The theoretical derivation of 1D Morlet Wavelet Transform method is given. The 1D Morlet Wavelet Transform method shows a better performance compared with that of Fourier Transform method.